1998
DOI: 10.1182/blood.v92.9.3082.421k15_3082_3089
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Intravenous Dexamethasone in Children With Mild to Moderately Severe Acute Chest Syndrome Complicating Sickle Cell Disease

Abstract: Acute chest syndrome (ACS) in patients with sickle cell disease (SCD) has historically been managed with oxygen, antibiotics, and blood transfusions. Recently high-dose corticosteroid therapy was shown to reduce the duration of hospitalization in children with SCD and vaso-occlusive crisis. Therefore, we chose to assess the use of glucocorticoids in ACS. We conducted a randomized, double-blind placebo-controlled trial to evaluate the efficacy and toxicity of intravenous dexamethasone (0.3 mg/kg every 12 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
3
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 39 publications
3
83
3
1
Order By: Relevance
“…The role of corticosteroids in the treatment for ACS is controversial. A small, randomized, controlled trial (82) demonstrated that corticosteroid administration resulted in the rapid resolution of mild-to moderate-ACS episodes. A short course of dexamethasone therapy may attenuate the course of ACS of sickle cell disease, but it also increases the risk of early readmission after discharge.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The role of corticosteroids in the treatment for ACS is controversial. A small, randomized, controlled trial (82) demonstrated that corticosteroid administration resulted in the rapid resolution of mild-to moderate-ACS episodes. A short course of dexamethasone therapy may attenuate the course of ACS of sickle cell disease, but it also increases the risk of early readmission after discharge.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…A clinical trial of hydroxyurea revealed that leukocyte counts correlated strongly with pain crisis rates (32). Acute vasoocclusive crisis has been precipitated inadvertently by administration of granulocytosis-inducing growth factors to sickle patients (1,5,138,191), and antiinflammatory steroids have an ameliorating effect on pain crisis (62) and acute chest syndrome (18). Acute painful episodes are not uncommonly accompanied by fever.…”
Section: Clinical Correlationmentioning
confidence: 99%
“…The median storage duration of the oldest unit of transfused RBCs was 17 days (interquartile range [IQR], [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], with a range of 2 to 41 days. When evaluated as a categorical variable, 36.8% of the transfused units were stored for less than 14 days, 25.6% were stored between 14 and 20 days, 17.1% were stored between 21 and 27 days, and 20.5% were stored for 28 days or more.…”
Section: Resultsmentioning
confidence: 99%
“…A validated ACS severity score does not exist, so a combination of reported severity scores and clinical experience was used to create the score depicted in Table 1. 24,25 A history of asthma was determined by reviewing diagnoses and past medical history in the medical records. Concomitant complications were included if the diagnosis was documented by a provider or there was a confirmatory laboratory result.…”
Section: Methodsmentioning
confidence: 99%